Development of solar powered pneumatic grain/seed cleaning system - ALKA MISHRA; J P SINHA; J K SINGH; B S TOMAR (The Indian Journal of Agricultural Sciences, 2018)
Vegetables are important constituents of Indian agriculture and nutritional security due to their short duration, high yield, nutritional richness, economic viability and ability to generate on-farm and off-farm employment. Despite being the second largest producer of vegetables in world, India lags far behind in its productivity in comparison to developed countries. The major challenge, which lies ahead, is to harness maximum yield potential as well as reduce production cost to enhance quality and productivity of vegetables under reducing land, declining natural resources and increasing biotic and abiotic stresses.The most of seed industry grow seeds at farmers' field. The farmers do not have primary processing machines or situated at uninsured grid power remote places. In this situation, either produced seed get damage or exploited by seed industries. In this context, a solar powered pneumatic grain/seed cleaning system was developed with specific functional, structural and operational design parameters. The developed pneumatic cleaner was tested for garden pea, bottle gourd, sponge gourd and radish seed lots of different impurity levels. It was found that the processed lot achieved more than 99% physical purity irrespective of type of seed and impurity levels. The cleaning efficiency of the system was more than 96%. The throughput capacity was observed to be garden80, 50 and75 kg/h for pea, battle gourd and radish respectively.